PENDIDIKAN KESEHATAN TENTANG PENTINGNYA KESEHATAN REPRODUKSI PADA REMAJA SANTRI DI PONDOK PESANTREN NURUL JADID - Sri Astutik Andayani (STIKES NGUDIA HUSADA MADURA, 2022)
IDHS data (2012) showed that 32.1% of girls and 36.5 boys aged 15-19 years started dating before the age of 15, around 0.7% of girls and 4.5% of boys aged 15-19 years had pre-marital sex, 7% of adolescent girls 15-19 years had given birth, and 2.8% of adolescents aged 15-19 years were involved in drug abuse. The role of adolescent students is important in this regard as providers of Adolescent Reproductive Health (KRR) education in Islamic boarding schools. The purpose of this community service activity is to educate young students about the importance of reproductive health. The method used is by way of counseling. Partners with the Nurul Jadid Islamic Boarding School in Probolinggo. The results obtained are that most of the young students understand the importance of reproductive health. To further maximize educational outcomes, it is highly recommended to conduct studies related to the obstacles faced by adolescents in carrying out reproductive care so that they can build more appropriate programs. Keywords: reproductive health, adolescent, knowledge